2015
DOI: 10.1021/cm503908g
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic High Performance Surface Anchored Metal−Organic Framework Bragg Reflector for Optical Sensing

Abstract: SE analyses were performed for HKUST-1 and ITO thin films on a Woollam M-44 ellipsometer at a fixed incidence angle of 75° on silicon wafers as substrates, in the range 400-750 nm, see Figure S1a. Modeling, fitting, and regression of the ellipsometric data were performed using the VASE software provided by the manufacturer. For the numerical calculations and PBG simulations the program WINCPC was used based on the experimental nk.-files from the Woollam M-44 ellipsometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 32 publications
1
58
1
1
Order By: Relevance
“…That H 2 storage is possible for MOF-5 within the interior of the printed composite is indicative that our composites are different from materials that incorporate MOFs by synthesizing them on the outside of some preformed, or printed, substrate. [10][11][12][13][14] Future studies in which MOFs are incorporated into 3D printing polymers in their non-degraded states will feature a more complete analysis of the interior pore structure found in the composite materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…That H 2 storage is possible for MOF-5 within the interior of the printed composite is indicative that our composites are different from materials that incorporate MOFs by synthesizing them on the outside of some preformed, or printed, substrate. [10][11][12][13][14] Future studies in which MOFs are incorporated into 3D printing polymers in their non-degraded states will feature a more complete analysis of the interior pore structure found in the composite materials.…”
Section: Resultsmentioning
confidence: 99%
“…That H 2 storage is possible for MOF-5 within the interior of the printed composite is indicative that our composites are different from materials that incorporate MOFs by synthesizing them on the outside of some preformed, or printed, substrate. [10][11][12][13][14] Future studies in which…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MOFs have shown great potential for the removal of carcinogenic polycyclic aromatic hysdrocarbons (PAHs), heavy metals, pesticides, dyes, radionucludes and other toxic chemicals [159][160][161][162][163][164][165]. Introducing additional functionality via magnetic nanoparticles can be achieved by synthesising magnetic framework composites (MFCs) [166].…”
Section: Sequestration Of Pollutantsmentioning
confidence: 99%
“…Liu et al have recently reported on BSs, which comprise of several alternating layers of HKUST-1 SURMOFs and ITO, where the HKUST-1 and ITO layers are obtained by the LPE-based method and by a conventional sputter process, respectively [70]. In this example, HKUST-1 is the material with the low RI, whereas the sputtered ITO represents the high RI material.…”
Section: Electronic Propertiesmentioning
confidence: 99%